Pembelajaran Berbasis Elektronik (Besmart Elearning) sebagai Alternatif Strategi Pembelajaran dalam Mata Kuliah Pendidikan - Sataroh, Sindy; Hidayati, Dian; Ridwan, Ahmad (UMSU, 2024)
The purpose of this study is to determine students' understanding of Besmart Elearning-based learning, student preparation in participating in Besmart Elearning-based learning and the obstacles experienced by students in implementing Besmart Elearning-based learning. This research approach is qualitative using data collection techniques through interviews and literature studies. The results of the study show that students' understanding of Besmart Elearning in Pancasila education courses has the same view that learning is effective, efficient and that learning materials are systematically arranged, so that students can easily understand and access them. Preparation of students in taking part in besmart elearning-based learning must have mature readiness, both in terms of technology and media components in the form of computers, laptops and adequate internet access. Besides that, prepare yourself with fresh and consistent intentions, hearts, minds. Students also prepare learning resources in learning. The obstacles experienced by students are that students have very diverse obstacles. Constraints on the unsupported internet network and server down because the database server is overloaded due to the large number of users accessing it and the signal is not supported. The rest of the electronic-based learning (Besmart Elearning) in Pancasila education courses is easily accessible to students.